The study of the Spatholobus decoction on improving the maximal oxygen uptake of track and field athletes - Feng Jiacheng; Niu Qimeng; Zhang Zhiwu (BIO Web of Conferences, 2023)
Objective: It aims to observe the effect of Spatholobus decoction on the maximum oxygen uptake of athletes.This is of great significance to improve the endurance of athletes. Methods: Male sprint athletes in sports schools were randomly divided into a control group, and three experimental groups. The experiment period lasted for four weeks, and four groups ran 5,000 meters once a day, including warm-up and training. The second and fourth groups were given suberect Spatholobus decoction at a ratio of 2ml/kg according to the body weight of the participants. The control group and the third group received the same dose of water. Fasting blood biochemical indexes were determined at 8 a.m. the day before and the day after the experiment. The VO2 maximum load test was carried out on the same day. Half a year later, the same experiment was done by switching the control group and the fourth group, and the second group switched to the third group. Statistical data are collected and analyzed using SPSS analysis systemResults -(1) The correlation values of red blood cells in the second group had an obvious decreasing trend (P<0.05), but the results of the VO2max loading test had no change. (2) Leukocyte of the third group was significantly increased (P<0.05); the VO2 maximum load test showed a significant increase in respiratory quotient and vco2. P<0.05). (3) The blood biochemical indexes of the fourth group had no significant changes, but the VO2max (P<0.01), VCO2max (P<0.05) and the maximum detection time (P<0.05) were increased significantly. Conclusion: Spatholobus decoction can improve the oxygen delivery capacity of red blood cells and increase the VO2 max of endurance trainers under the condition of blood biochemical index balance.